Palenie ksiąg w starożytnym Rzymie jako przejaw autorytarnego ograniczania republikańskiej wolności słowa - Nowicka, Dobromiła (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Transition from republic to principate brought a meaningful alteration in the area of conceiving freedom of speech. Republican standards in this matter were not apt for the new regime as it was too fragile to withstand the republican dissidence. New restrictions and ad hoc measures needed to be applied. Among them burning of books was of particular importance. The article deals with incidents of book burning in the times of Augustus (cases of Titus Labienus and Cassius Severus) and Tiberius (those of Mamercus Scaurus and Cremutius Cordus), which, although not numerous, were of high significance for freedom of speech within the new regime. On the basis of analysis of selected ancient sources and scientific literature on the matter, an answer to the question about their political meaning is sought. Accordingly, the socio-political background of change in the area of freedom of speech in the context of passing from a republic to the authoritarian regime of a principate needs to be taken into account. Unfortunately, historical sources regarding the matter are deeply unequivocal and scientific interpretations seem strongly conditioned by tendencies to discern crimen maiestatis in every case of book burning from the times of early empire, even if it is not plainly attested by ancient authors. It appears that the subsequent popularity of maiestas charges could have influenced the erroneous interpretation of previous incidents, which appear to have been — at least formally — distant from the law of injured majesty, being ad hoc measures at least in the times of the reign of Augustus. However, the essential point of analysis concerns the grounds of the incidents of burning books that took place under August and Tiberius, showing a step-by-step process of supressing the republican freedom of speech. Although rare, book burnings reflect a common tendency in new authoritarian rulers’ politics, which at first tend to deal with opponents unpopular among the aristocracy, only to move on to managing adversaries originating from the Roman élite. Nevertheless, the undertaken measures were not suitable for annihilating the books in question, contributing to their growth in popularity. The answer to the core question about the aims of book burnings under Augustus and Tiberius seems to boil down to mere propaganda, showing that dissident books would not be tolerated, no matter the social status of their authors.
Keywords: book burning; freedom of speech; principate; crimen maiestatis